1998
DOI: 10.1136/ard.57.4.203
|View full text |Cite
|
Sign up to set email alerts
|

Associations of radiological osteoarthritis of the hip and knee with locomotor disability in the Rotterdam Study

Abstract: Objective-To assess the contribution of radiological osteoarthritis of the hips and knees to disabilities in the activities of daily living related to lower limb function. Methods-During a home interview 1156 men and 1739 women, randomly chosen from the source population of all independently living residents aged 55 years and over living in a district of Rotterdam (the Rotterdam Study) were asked about locomotor disability by six questions of the Health Assessment Questionnaire (HAQ) and about pain in the hips… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
135
3
9

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 185 publications
(161 citation statements)
references
References 11 publications
14
135
3
9
Order By: Relevance
“…An additional five studies [7,22,23,38,54] were identified from reference lists of included studies. The 23 studies included 13 cross-sectional studies [1, 7, 9, 19, 23, 27-31, 43, 54, 55], six cohort studies [5,22,44,[47][48][49], one case-control study [3], and three previous review articles on this topic [26,36,38]. Older estimates of the prevalence of radiographic primary hip OA reported in the latter group were used to supplement those uncovered by our electronic search.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…An additional five studies [7,22,23,38,54] were identified from reference lists of included studies. The 23 studies included 13 cross-sectional studies [1, 7, 9, 19, 23, 27-31, 43, 54, 55], six cohort studies [5,22,44,[47][48][49], one case-control study [3], and three previous review articles on this topic [26,36,38]. Older estimates of the prevalence of radiographic primary hip OA reported in the latter group were used to supplement those uncovered by our electronic search.…”
Section: Methodsmentioning
confidence: 99%
“…The most common method used to diagnose overall prevalence of radiographic primary hip OA was that of Kellgren and Lawrence (K&L) (n = 23) [5,19,23,26,27,29,33,37,38,43,44,[47][48][49]54] followed by minimum joint space width (JSW) (n = 10) [3,9,26,28,30,43,49] and other classification schemes such as the Croft index (n = 2) [55], the American College of Rheumatology criteria (n = 1) [1], the Atlas of Osteoarthritis criteria (n = 1) [38], and unspecified methods (n = 2) [26]. The CV for the K&L method of diagnosis was 97.4% for K&L Grade C 2 and 73.1% for K&L C 3; the Croft C 3 method of diagnosis had a CV of 113.6%.…”
Section: Prevalence By Methods Of Diagnosismentioning
confidence: 99%
See 3 more Smart Citations